Early aldosterone up-regulated genes: new pathways for renal disease - Kellner, Markus; Peiter, Angela; Hafner, Mathias; Feuring, Martin; Christ, Michael; Wehling, Martin; Falkenstein, Elisabeth; Lösel, Ralf M. (Kidney international, 2003)
Early aldosterone up-regulated genes: New pathways for renal disease? Background - The use of aldosterone antagonists has important beneficial effects on the progression of renal and cardiac disease reflected in a decrease of cardiovascular mortality and renal failure. Nevertheless, the incidence of heart and end-stage renal failure continues to increase. This leads to the conclusion that mechanisms independent of the classical aldosterone/mineralocorticoid receptor system may contribute to the pathogenesis of cardiac and renal disease. - Methods - The mRNA expression profile of human renal epithelial cells in response to aldosterone was characterized using cDNA arrays covering ∼1430 genes. Differentially expressed genes were further evaluated by quantitative reverse transcription-polymerase chain reaction (RT-PCR), Northern blotting, and estimating the gene products by Western blotting. - Results - Aldosterone treatment of cells resulted in significant up-regulation of several genes within 1 hour, with sgk, p21/waf1, gadd45, and gadd153 being the most significant ones. Long-term treatment (>4 hours) with aldosterone induced the mRNA expression of pparα and purα. The mineralocorticoid receptor inhibitor spironolactone decreased the mRNA levels of sgk, p21/waf1, and gadd45, whereas the glucocorticoid receptor inhibitor RU 486 reduced the mRNA level of sgk and p21/waf1. Gadd153 was not affected by any of the inhibitors, probably indicating regulation by nonclassic mechanisms. - Conclusion - Among the early genes investigated in this study, one transcript has been identified that is not suppressed by antagonists of either glucocorticoid or mineralocorticoid receptor. Further studies should be able to identify other genes regulated in a similar manner that could explain the inefficacy of spironolactone in some cases of aldosterone-mediated kidney disease.